The Impact of Student Teams Achievement Divisions (STAD) Learning Method on Long Jump Performance - Dewi Septaliza; Edi Sopran Lubis (UNIB Press, 2023)
This research aims to investigate the influence of the Student Team Achievement Divisions (STAD) learning method on students' long jump performance. The STAD learning method is an approach that encourages collaboration and interaction among students in the form of teams, with a focus on both group and individual achievements. Long jump was chosen as the research context due to its involvement in complex physical and technical aspects, requiring a combination of motor skills and conceptual understanding. The research method used is an experimental method, with a